Tetraketide α-pyrone reductases in sporopollenin synthesis pathway in Gerbera hybrida: diversification of the minor function - Zhu, Lingping; Zhang, Teng; Teeri, Teemu H. (Horticulture research, 2021)
The structurally robust biopolymer sporopollenin is the major constituent of the exine layer of pollen wall and plays a vital role in plant reproductive success. The sporopollenin precursors are synthesized through an ancient polyketide biosynthetic pathway consisting of a series of anther-specific enzymes that are widely present in all land plant lineages. Tetraketide α-pyrone reductase 1 (TKPR1) and TKPR2 are two reductases catalyzing the final reduction of the carbonyl group of the polyketide synthase-synthesized tetraketide intermediates to hydroxylated α-pyrone compounds, important precursors of sporopollenin. In contrast to the functional conservation of many sporopollenin biosynthesis associated genes confirmed in diverse plant species, TKPR2 ’s role has been addressed only in Arabidopsis, where it plays a minor role in sporopollenin biosynthesis. We identified in gerbera two non-anther-specific orthologues of AtTKPR2 , Gerbera reductase 1 ( GRED1 ) and GRED2 . Their dramatically expanded expression pattern implies involvement in pathways outside of the sporopollenin pathway. In this study, we show that GRED1 and GRED2 are still involved in sporopollenin biosynthesis with a similar secondary role as AtTKPR2 in Arabidopsis. We further show that this secondary role does not relate to the promoter of the gene, AtTKPR2 cannot rescue pollen development in Arabidopsis even when controlled by the AtTKPR1 promoter. We also identified the gerbera orthologue of AtTKPR1 , GTKPR1 , and characterized its crucial role in gerbera pollen development. GTKPR1 is the predominant TKPR in gerbera pollen wall formation, in contrast to the minor roles GRED1 and GRED2. GTKPR1 is in fact an excellent target for engineering male-sterile gerbera cultivars in horticultural plant breeding.